2020
DOI: 10.1111/ijac.13641
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial applications and safety issues of silica‐based materials: A review

Abstract: As the problem of bacterial contamination continues to grow in its significance, researchers have reported many antibacterial materials that are based on inorganic compounds. Of these, materials that are based on silica and its derivatives have been widely used in engineering, medicine, and food. This paper reviews the advantages, safety issues, and applications of silica and its derivatives, as reported in recent years. The information provided highlights the preparation, application, and antimicrobial effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 125 publications
0
15
0
Order By: Relevance
“…The thickness of the inhibition zone for 20, 40, and 80 μg/mL concentrations were obtained, 0, 7.77, and 8.44 mm, respectively. Appeared halos around the filter paper disks should be due to the interaction between nanoparticles and bacterial surface proteins in such a way that, it can change the properties of proteins on the surface of bacteria and inhibit the growth of bacterial cells (Tian & Liu, 2020). In the following, antibacterial ability of Au@SiO 2 nanostructures was investigated and the results were compared with the ability of bare SiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the inhibition zone for 20, 40, and 80 μg/mL concentrations were obtained, 0, 7.77, and 8.44 mm, respectively. Appeared halos around the filter paper disks should be due to the interaction between nanoparticles and bacterial surface proteins in such a way that, it can change the properties of proteins on the surface of bacteria and inhibit the growth of bacterial cells (Tian & Liu, 2020). In the following, antibacterial ability of Au@SiO 2 nanostructures was investigated and the results were compared with the ability of bare SiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…A number of rare earth metal oxides have been reported to possess strong antibacterial potentials against multiple drug resistance bacterial strains (Arshad et al, 2019;Rabiee et al, 2022). In this regard herein, antibacterial activity of silica and Au@SiO 2 has been specially the filter paper disks should be due to the interaction between nanoparticles and bacterial surface proteins in such a way that, it can change the properties of proteins on the surface of bacteria and inhibit the growth of bacterial cells (Tian & Liu, 2020). In the following, antibacterial ability of Au@SiO 2 nanostructures was investigated and the results were compared with the ability of bare SiO 2 nanoparticles.…”
Section: Antimicrobial Properties Of Sio 2 and Au@sio 2 Nanostructuresmentioning
confidence: 95%
“…In order to kill bacteria, the drug must be able to cross the cell membrane and enter the bacteria to produce its effect. In the literature, it has been hypothesized that the silica interact with certain proteins present on the surface of bacteria and thus may open some channels on the surface which cause the drug substance to enter smoothly inside bacteria, thereby killing them [35]. Similarly, some researchers simply proposed that the combination of the antibacterial agent with SiO 2 may have a synergistic effect on killing bacteria [36].…”
Section: In Vivo Antibacterial Studiesmentioning
confidence: 99%
“…In addition, large numbers of swipes or touches on the screen cause poor mechanical durability of metal nanoparticles on the display, owing to their weak adhesion. Many recent studies have revealed the antibacterial activity of various metal oxide nanoparticles such as ZnO, CuO, TiO 2 , and Fe 2 O 3 . However, metal oxide nanoparticles prepared using a solution method usually display inhomogeneous antibacterial effect and lowered transmittance due to the severe agglomeration of the nanoparticles, whereas metal oxide thin films prepared by sputtering exhibit excellent antibacterial activity and mechanical durability …”
Section: Introductionmentioning
confidence: 99%